Pemberdayaan Masyarakat melalui Wirausaha Kerupuk Bonggol Pisang di Kabupaten Sukoharjo - Sholichah Rohmani; Adi Yugatama (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
One effort that can be done by housewives is entrepreneurship to make crackers. Food products from banana trees were chosen because they have good prospects, besides the fruit there are other parts that can be used, namely banana humps. Because of the benefits and high nutritional content, it is necessary to diversify from banana humps to be sold. The purpose of this activity is to inspire partners about the idea and spirit of entrepreneurship using sources of raw materials that are easy to obtain, so they can increase income. The program is carried out through two stages, namely processing banana humps into healthy crackers and transferring packaging technology. This activity was carried out in the training and development of technology for processing banana humps into cracker products, which could be an alternative economic new business in the community. The positive impact of this activity is the increasing skills and knowledge of partners about making food from banana trees, as well as improving the skills of packaging techniques. There is an increase in the ability of entrepreneurial partners in producing and selling products.